Pendidikan Anak Usia Dini dalam Perkembangan Tekhnologi: Peran Kurikulum Ramah Anak dan Literasi Artificial Intelligence - Nurul Qomariyah, Nurul Qomariyah; Masti Yanto; Fathorrozy (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Abstract Early childhood learning (PAUD) is an important stage in forming the foundations of child development. However, in an era where technology is developing rapidly, the challenges for the quality of early childhood learning are increasingly complex. This article proposes a strategy to improve the quality of PAUD learning by paying attention to technological developments, especially artificial intelligence (AI) literacy, as well as implementing a child-friendly curriculum. Through library research using a content analysis approach, this research reveals that The role of a child-friendly curriculum is to ensure that the learning process is appropriate to the needs and developmental stages of early childhood. This curriculum does not only focus on academic aspects, but also integrates social, emotional learning and relevant life skills. Apart from that, AI literacy is an important aspect in the context of future learning. Children need to be introduced to basic concepts about artificial intelligence and related technologies, so that they can become intelligent and critical users in facing future technological challenges. Effective early childhood education must be able to accommodate the dynamics of current technology while still paying attention to the child's overall needs and development stages.